2015
DOI: 10.14507/epaa.v23.1752
|View full text |Cite
|
Sign up to set email alerts
|

Are Teachers Crucial for Academic Achievement? Finland Educational Success in a Comparative Perspective

Abstract: Teachers are seen as the main reason behind the high, equal, and consistent student performance in Finland as measured by the Programme for International Student Assessment (PISA), and there is a lot of truth in this. Candidates for teacher training programs are selected through a rigorous process, for example. However, using primarily the case of Finland, this paper seeks to show that factors beyond the quality of teachers are also involved in explaining high performance on international standardized tests by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
(27 reference statements)
0
10
0
6
Order By: Relevance
“…Beginning with the release of the first set of PISA exam scores in 2001, Finland's international reputation began to shine brightly-Finnish 15-year-olds were collectively at, or near, the top in all three tested subject areas-mathematics, reading, and science literacy (Andere, 2015;Hargreaves & Shirley, 2011;Sahlberg, 2014;Simola, 2015). 1 Finland's stellar performances on the PISA exams, however, were not the reason for the study I conducted with Finnish educators in the late summer of 2015.…”
Section: Teaching For Civil Society In Finland: a Canadian Perspective On Finnish Educators' Reflectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beginning with the release of the first set of PISA exam scores in 2001, Finland's international reputation began to shine brightly-Finnish 15-year-olds were collectively at, or near, the top in all three tested subject areas-mathematics, reading, and science literacy (Andere, 2015;Hargreaves & Shirley, 2011;Sahlberg, 2014;Simola, 2015). 1 Finland's stellar performances on the PISA exams, however, were not the reason for the study I conducted with Finnish educators in the late summer of 2015.…”
Section: Teaching For Civil Society In Finland: a Canadian Perspective On Finnish Educators' Reflectionsmentioning
confidence: 99%
“…That said, it is still the case that there is very 24(1) Spring 2018 little Finnish research being done on its own school system (Sahlberg, 2014), and that which pertains to teaching about social class, the commons, and immigration is almost non-existent. Some Finnish scholars have examined the role of teachers in student achievement (Andere, 2015;Sahlberg, 2006;Simola, 2005). A recent study about educating for democracy in England and Finland found that in schools in both countries citizenship education is being increasingly replaced by neoliberal initiatives such as economic growth and productivity (Raiker & Rautiainen, 2016).…”
Section: The Literature On the Role Of Finland's Teachers Within Finnish Civil Societymentioning
confidence: 99%
“…Many of these articles have linked the well-performing students to the highly qualified teachers, who need to have a Master's degree for a permanent position. In particular, it has been argued that, in Finland, being a teacher is one of the most prestigious occupations, as evidenced by the fact that only the best and most motivated students are admitted to the teacher training programs as well as the observation that Finnish teachers enjoy a very high status in society (Morgan 2014, Sahlberg 2011, Linnakylä et al 2011, OECD 2011, Andere 2015.…”
Section: The Finnish Educational System and The Pisamentioning
confidence: 99%
“…Con miradas todavía más amplias pero no por ello inconvenientes, se ha hecho notar desde países como Finlandia cuyas políticas de profesorado y formación son admiradas por doquier, que las condiciones laborales de la profesión y sus efectos sobre los aprendizajes del alumnado han de ponerse en relación con un entorno socio-ecológico docente participado no solo por la valoración social y cultural de sus profesores, sino también por una apuesta del país por una calidad justa y equitativa (Andere, 2015).…”
Section: Una Mirada Más Amplia Sobre Colaboración Docenteunclassified